Analisis Koreksi Fiskal untuk Menentukan Besarnya Pajak Terutang pada PT Furaya Transport - Helena Cicilia; Hamdani Arifulsyah; Tobi Arfan (Politeknik Caltex Riau, 2015)
Fiscal correction is done by adjusting all income and expenses in the commercial income statement with tax regulations, resulting in a fiscal financial statements will be used as a basis in determining the tax payable. The case study of this research was conducted at PT Furaya Transport engaged in timber transport services. PT Furaya Transport has made fiscal correction for fiscal year 2013, but there are some accounts that are not corrected by the company. In the calculation of tax payable for the year 2014, the accounts that contained in the commercial income statement are adapted to tax regulations. The result showed PT Furaya Transport’s profit before fiscal correction is Rp 2.215.903.888,-. After the fiscal correction in accordance with applicable tax regulations, the amount obtained Rp 3.102.159.917,- of positive correction and Rp 2.011.809.275,- of negative correction, so the taxable income is Rp 3.306.254.530,- with tax payable amounted to Rp 768.455.936,-Key word : commercial income statement, fiscal income statement, income tax payable corporate tax payers